Severe falciparum malaria and acquired childhood language disorder. - Carter, J; Lees, J; Gona, J; Murira, G; Rimba, K; Neville, BG; Newton, C (2006)
Language disorders have been reported after severe falciparum malaria but the deficits have not been described in detail. We assessed language outcome in three groups of children aged 6 to 9 years (n=487): those previously admitted to Kilifi District Hospital, Kenya, with cerebral malaria (CM; n=152; mean age 7y 4 mo [SD 1y 1mo]; 77 males, 75 females); or those with malaria and complicated seizures (M/S; n=156; mean age 7y 4mo [SD 1y 2mo]; 72 males, 84 females); and those unexposed to either condition (n=179; mean age 7y 6mo [SD 1y 1mo]; 93 males, 86 females). Median age at hospital admission was 28 months (interquartile range [IQR] 19 to 44 mo) among children with a history of CM and 23 months (IQR 12 to 35mo) among children with a history of M/S. A battery of eight assessments covering the major facets of speech and language was used to measure language performance. Cognitive performance, neurological/motor skills, behaviour, hearing, and vision were also measured. Eighteen (11.8%) of the CM group, 14 (9%) of the M/S group, and four (2.2%) of the unexposed group were found to have a language impairment. CM (odds ratio 3.68, 95% confidence interval 1.09 to 12.4, p=0.04) was associated with significantly increased odds of an impairment-level score relative to the unexposed group. The results suggest that falciparum malaria is one of the most common causes of acquired language disorders in the tropics.